Agreement of Corneal Diameter Measurements Obtained by a Swept-source Biometer and a Scheimpflug-based Topographer. Issue 11 (November 2017) - Salouti, Ramin; Nowroozzadeh, Mohammad Hossein; Tajbakhsh, Zahra; Bagheri, Mansoureh; Ghoreyshi, Maryam; Azizzadeh, Monir; Razeghinejad, Mohammad Reza
Abstract : Purpose: To assess the agreement between a swept-source optical biometry device (IOLMaster 700) and a Scheimpflug-based topography device (Pentacam HR) in measuring the corneal diameter. Methods: A total of 100 eyes from 100 cataract surgery candidates were enrolled. The white-to-white (WTW) distance measurements provided by both devices were recorded and analyzed. A paired t test was performed to compare the mean values of the WTW distance between the IOLMaster 700 and Pentacam HR. The Bland–Altman analysis was used to evaluate the agreement between the measurements of both devices. Results: Mean age (±SD) of the participants was 65.9 ± 3.3 years, and 58 (58%) were men. The mean WTW distances measured by the IOLMaster 700 and Pentacam HR were 11.72 ± 0.45 mm and 11.41 ± 0.42 mm, respectively ( P < 0.001). The overall 95% limits of agreement were −0.17 and 0.78 mm. The 95% limits of agreement between the measurements of the 2 devices were −0.30 and 0.84 versus −0.07 and 0.72 for eyes with WTW distances of ⩽11.50 mm versus >11.50 mm, respectively. Conclusions: According to the results of this study, the IOLMaster 700 may overestimate the WTW distance measurements by up to 0.78 mm compared with the Pentacam HR, so these 2 devices should not be used interchangeably for this purpose. The agreement is somehow weaker for eyes with WTW distances of 11.50 mm or less than those with WTW distances greater than 11.50 mm.